Thinking like a leader the TILL system - Sydow-Campbell, Kim (IEEE, 2010)
Course content reaffirmed: 06/2015--The system of leadership communication introduced in this course is designed to increase your ability to influence people. This system, called TILL, was introduced in the book, Thinking & Interacting Like a Leader. In essence, the system focuses on interpersonal communication skills. However, it addresses any situation in which a manager delivers a message to organization members, whether that message is delivered face-to-face, in writing or electronically